BUILDING TRUST THROUGH TRANSPARENCY: NAVIGATING THE FUTURE OF AI-GENERATED MARKETING CONTENT - Yunus, Fauziah Mohamad; Abas, Nurliyana; Azman, Azlin (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Dynamic nature of digital marketing has increased brand interaction with consumers through use of Artificial Intelligence (AI) tool. Nevertheless, as the use of AI-generated content has risen, there has been concern around whether consumers would trust such information, particularly in regard to transparency, the quality content, and the ethical responsibility of the consumer. Despite AI being easy and personal, it will raise suspicion when consumers are not sure of how the content has been developed. This conceptual paper proposes to develop a theoretical framework that can explain the interrelationship between AI transparency, contents quality and ethical factors, including fairness, bias and privacy to identify consumer trust in marketing communication. The study shows that there may be three dominant factors that motivate trust: avoidance of excessive disclosure of contributions, maximisation of quality of information disclosed, relevant and perceived quality of AI-generated content, and ethics protecting consumer interest. Results indicate that disclosure can lead to higher trust; however, a degree of too much or more technical information can overwhelm consumers. Equally, the value of content, in particular to the feeling importance and relevance thereof, is a main determinant of favourable disposition whereas moral factor is an imperative of hedging against sustainable trust. The paper makes an impact on the practical initiative that guided by marketers as it suggests consumer-oriented AI disclosure, excellent content plans, and ethical proactive phases of governance. In theory, it integrates the signalling theory, elaboration likelihood, and AI ethics into a multi-level framework of trust development. Although limited by the purely conceptual material, the framework will have an empirical foundation drawn across industry and cultures and will create awareness that the proper use of AI must be transparent, quality, and ethically upright in order to create consumer confidence, rather than to question it.